1981
DOI: 10.1210/jcem-52-5-988
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in Human Plasma: Correlation with Neurophysin and Stimulation with Estrogen*

Abstract: RIA for the measurement of oxytocin in human plasma is described. Extraction of oxytocin from larger peptides in plasma used acetone precipitation with a 75% +/- 2 SEM recovery of oxytocin. Nonspecific binding of the assay was less than 4%, and the minimum level of detection was 0.2 microunits/tube. No cross-reactivity was noted with neurophysins, arginine, or lysine vasopressin. The mean basal level (+/- SEM) of oxytocin in men was 1.80 +/- 0.07 microunits/ml and was not different in normal women (1.71 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
2
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(96 citation statements)
references
References 19 publications
2
91
2
1
Order By: Relevance
“…) on Day 6 of the normal primate luteal phase did not alter corpus luteum function, suggesting a local rather than systemic effect of oxytocin. Auletta et al (1984) (Amico, Seif & Robinson, 1981), stimulate PGF-2a release from the corpus luteum-bearing ovary in the monkey (Auletta et al, 1978), and induce oxytocin receptors in the endometrium (Roberts, McCracken, Gavagan & Soloff, 1976;McCracken, 1980). These observations suggest that oestrogens may be the biochemical signal responsible for the synthesis and release of PGF-2a and oxytocin.…”
Section: Resultsmentioning
confidence: 99%
“…) on Day 6 of the normal primate luteal phase did not alter corpus luteum function, suggesting a local rather than systemic effect of oxytocin. Auletta et al (1984) (Amico, Seif & Robinson, 1981), stimulate PGF-2a release from the corpus luteum-bearing ovary in the monkey (Auletta et al, 1978), and induce oxytocin receptors in the endometrium (Roberts, McCracken, Gavagan & Soloff, 1976;McCracken, 1980). These observations suggest that oestrogens may be the biochemical signal responsible for the synthesis and release of PGF-2a and oxytocin.…”
Section: Resultsmentioning
confidence: 99%
“…A role for gonadal steroids in regulation of VP and OT secretion was suggested by early reports of gender differences in plasma VP and stimulation of OT release by estrogen (Skowsky et al, 1979;Amico et al, 1981). However, disparate results from gonadectomy and hormone replacement studies and opposite actions of gonadal steroids in vivo and in vitro made the role of gonadal steroids unclear (Crowley and Amico, 1993;Swenson and Sladek, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, plasma OT concentrations remain low throughout the pregnancy and birth. However, estradiol treatment results in increased circulating oxytocin levels (Mitchell et al, 1998;Amico et al, 1981). Klarenbeek et al (2007) demonstrated in dogs that OT concentrations remain low at the end of pregnancy, increasing only during the expulsion stage of vaginal labor.…”
Section: Discussionmentioning
confidence: 99%